Analyzing the Sources of Noise in Internal Combustion Engines - Am Quoc Do (Journal of Technical Education Science, 2025)
Internal combustion engines are extensively used in various modes of transportation, including ships and cars. However, their operation generated significant noise, which can disrupt daily life and poses health risks. Prolonged exposure to noise can lead to insomnia, cardiovascular diseases, and even death, making noise pollution a growing social concern. As the primary power source and major noise contributor in ships and automobiles, internal combustion engines play a crucial role in overall noise levels. The noise produced by internal combustion engines stems from various sources and mechanisms within the engine. These includes the combustion process itself, mechanical interactions between engine components, and the exhaust system, ect. Each of these sources have specific causes and contributing factors. This work discusses and analyzes the sources of noise, their causes, and the factors that influence them. By addressing these key areas, it is possible to reduce the negative effects of engine noise on human health and well-being.